Presynaptic peptidergic modulation of olfactory receptor neurons in Drosophila. - Ignell, R.; Root, C.M.; Birse, R.T.; Wang, J.W.; Nässel, D.R.; Winther, A.M. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The role of classical neurotransmitters in the transfer and processing of olfactory information is well established in many organisms. Neuropeptide action, however, is largely unexplored in any peripheral olfactory system. A subpopulation of local interneurons (LNs) in the Drosophila antannal lobe is peptidergic, expressing Drosophila tachykinins (DTKs). We show here that olfactory receptor neurons (ORNs) express the DTK receptor (DTKR). Using two-photon microscopy, we found that DTK applied to the antennal lobe suppresses presynaptic calcium and synaptic transmission in the ORNs. Furthermore, reduction of DTKR expression in ORNs by targeted RNA interference eliminates presynaptic suppression and alters olfactory behaviors. We detect opposite behavioral phenotypes after reduction and over expression of DTKR in ORNs. Our findings suggest a presynaptic inhibitory feedback to ORNs from peptidergic LNs in the antennal lobe.